(untitled) (Journal of Rangpur Medical College, 2025)
Introduction: ST-elevation myocardial infarction (STEMI) remains a common cause of cardiovascular mortality, with accurate risk stratification for the appropriate management of the patient. Cardiac troponin I (cTnI) has been identified as a potential prognostic biomarker, as well as in its diagnostic role. Objective: This study aimed to evaluate the prognostic significance of cardiac troponin I level for in-hospital recovery and complications in patients with STEMI. Methods: A cross-sectional study was conducted on 100 STEMI patients aged 30-70 years. The patients were categorized into three groups based on serum troponin I concentration: <0.034 ng/mL (low risk), 0.034-0.12 ng/mL (intermediate risk), and _0.12 ng/mL (high risk). In-hospital mortality, complications (arrhythmia, heart failure, cardiogenic shock), and length of stay in the hospital were the primary outcomes of interest. Statistical analysis was performed on SPSS version 26 using chi-square tests and binary logistic regression. Results: The study population had a mean age of 52.5±13.1 years with 59% male preponderance. There was a clear-cut dose-response relation observed between troponin levels and adverse outcomes. In-hospital mortality increased step-wise in low, intermediate, and high-risk troponin groups (0%, 3.4%, 38.5% respectively; p<0.001). Cumulative complication rates also followed a similar pattern (3.7%, 68.4%, 100% respectively; p<0.001), with specific complications like arrhythmias (0%, 33.3%, 46.1%), heart failure (0%, 23.3%, 30.7%), and cardiogenic shock (1.3%, 11.6%, 23.0%). Hospital stay was also significantly related to the troponin levels, with prolonged hospitalization (>7 days) in 0%, 6.7%, and 76.9% in respective groups (p<0.001). Multivariate analysis also endorsed troponin _0.12 ng/mL as an independent predictor of mortality with a 49-fold increased risk (OR=49.8, 95% CI: 5.3-463.2, p<0.001). Conclusion: The study highlights the optimal prognostic value of cardiac troponin I levels in the prediction of in-hospital outcomes among STEMI patients. The proposed risk stratification system can be applied to inform decisions for clinical management, deployment of resources, and patient care approach in acute cardiac care units. J Rang Med Col. September 2025; Vol.10, No.2:3-7